KARAKTERISTIK SABUN SEREH PADA PERLAKUAN NISBAH KONSENTRASI MINYAK KELAPA – ASAM STEARAT DAN GULA PASIR HALUS – ETANOL - Cahyanty Nugraha, Febriyawati; Wartini, Ni Made; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
The purpose of this study were to determine the effect of ratio of coconut oil-stearic acid and can sugar-ethanol to the level of soap suds and textures lemongrass on the characteristic of lemongrass soap and to find out the ratio of coconut oil – stearic acid and can sugar – ethanol for producing the best characteristic of lemongrass soap. This research used a factorial randomized block design. The first factor was the ratio of coconut oil - stearic acid, which consists of three levels, namely: 0:29.2, 6:23.2, and 12:17.2 and the second factor was the ratio of can-sugar – ethanol, which consists of three levels ie : 5:26.3; 8:23.3; 11:20.3; and 13:18.3. Variables observed were the soap yield, levels of foam formation, texture, free fatty acids, free alkali, preference for foam formatio, texture, and aroma. The result showed that the interaction of both factors affected the level of foam formation of lemongrass soap. On the other hand, the texture of soap was only influenced by the single factor of coconut oil – stearic acid ratio or can sugar – ethanol ratio. The factors level that produced the best characteristics of lemongrass soap was the ratio coconut oil – stearic acid of 6 : 23,2 and the ratio of can-sugar – ethanol of 11 : 20,3. This combination factors level yielded the soap of about 84,89% with the level of foam formation, texture, free fatty acid, and free alkali were 91.91%, 22.70 mm/sec, 0.62%, and 0.17%, respectively. This soap characteristic complied with the Indonesia National Standard (SNI 06- 3532-1994). The level of panelist preference of the soap was rather like to like for foam formation, texture, and aroma.
Keywords: 64,